Skin microbiota-associated inflammation precedes autoantibody induced tissue damage in experimental epidermolysis bullosa acquisita. (April 2016) - Ellebrecht, Christoph T.; Srinivas, Girish; Bieber, Katja; Banczyk, David; Kalies, Kathrin; Künzel, Sven; Hammers, Christoph M.; Baines, John F.; Zillikens, Detlef; Ludwig, Ralf J.; Westermann, Jürgen
Abstract: Epidermolysis bullosa acquisita (EBA) is a chronic autoimmune blistering skin disease characterized by autoantibodies against type VII collagen (COL7). Immunization of SJL/J mice with recombinant murine COL7 results in break of tolerance and skin blisters. Strikingly, despite circulating autoantibodies, the same genetic background and identical environmental conditions, 20% of mice remain healthy. To elucidate the regulation of the transition from the presence of autoantibodies to overt autoimmune disease, we characterized the innate and adaptive immune response of mice that remain healthy after immunization and compared it to mice that developed skin disease. Both clinically healthy and diseased SJL/J mice showed circulating autoantibodies and deposition of complement-ﬁxing IgG2c autoantibodies and C3 at the dermal–epidermal junction. However, only in diseased animals significant neutrophil infiltration and increase in FcgRIV expression were observed in the skin. In contrast, the expression of T cell signature cytokines in the T cell zone of the draining lymph node was comparable between clinically healthy and diseased animals after immunization. Surprisingly, health was associated with a decreased expression of CD11c, TNFA and KC (CXCL1) in the skin prior to immunization and could be predicted with a negative predictive value of >80%. Furthermore, mice that did not develop clinical disease showed a significantly higher richness and distinctly clustered diversity of their skin microbiota before immunization. Our data indicate that the decision whether blisters develop in the presence of autoantibodies is governed in the skin rather than in the lymph node, and that a greater richness of cutaneous bacterial species appears to be protective. Highlights: CD11c, KC and TNFα predict outcome of experimental epidermolysis bullosa acquisita. Higher richness of skin microbiota is associated with development of EBA symptoms. T helper cell influence does not differ between healthy and EBA diseased mice.